1972
DOI: 10.1136/jmg.9.1.102
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the long arms of chromosome 18 (46,XX,18q-) associated with absence of IgA and hypothyroidism in an adult.

Abstract: London et al (1964) recorded the case of a 28-yearold woman who had menstrual periods for 5 years and then became amenorrhoeic. He assumed thai the XX cells had to be present for the ovaries tc function regularly as indicated by normal menstruation. If there is a lack of these XX cells primary amenorrhoea will occur and if the XX cells arc 'used up' then the amenorrhoea will be secondary. Summary A case is reported of a 20-year-old woman with a 45,X complement, with dwarfism and numerous other signs of Turner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Nongoitrous hypothyroidism has been reported in one adult female with E 18q- (19). The authors clearly state that 'hypothyroidism is not a characteris tic of the syndrome'.…”
Section: Discussionmentioning
confidence: 82%
“…Nongoitrous hypothyroidism has been reported in one adult female with E 18q- (19). The authors clearly state that 'hypothyroidism is not a characteris tic of the syndrome'.…”
Section: Discussionmentioning
confidence: 82%
“…There have been six patients with 18p-syndrome associated with hypothyroidism (Biihler et al, 1964;Ruvalcava, 1970;Malpuech et aI., 1971;Kistenmacher et al, 1973;Hasen and Bartalos, 1975;Gluckman, 1977), one 18p-patient with Graves disease (Jones and Carey, 1982), one 18q-patient with hypothyroidim (Faed et al, 1972), and one r(18) patient with hypothyroidism (Winter et al, 1972). Hypothyroidism in three of these six patients with 18p-, as in our four patients, had been attributed to autoimmune thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…IgA deficiency is frequently observed in 18p-or 18q-syndrome. A case of 18q-syndrome associated with absence of IgA and with hypothyroidism by Faed et al (1972) may have suggested a pathogenic relationship of IgA deficiency and the occurrence of hypothyroidism. However, the relationship is less likely, because all of our patients but Case 1 were not complicated with IgA deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Finland the deficiency occurs with a frequency of 1:400 in healthy persons [13] who may nevertheless have some other serological abnormalities too [14]. On the other hand, IgA deficiency may be connected with various disease states [3] and chromosomal defects [7,17].…”
Section: Introductionmentioning
confidence: 99%